Pengaruh Keadilan Organisasi, Kepuasan Kerja, dan Komitmen Afektif terhadap Organizational Citizenship Behavior - Permasih, Desty; Adriansyah, Ahmad (https://jurnal.binamandiri.ac.id/, 2021)
Human resource management is a critical aspect of improving quality in order to achieve the organization's vision. For existing resources to contribute appropriately and be loyal to the school, the school must also provide favorable treatment. Based on this, the authors are interested in examining positive attitudes in educational institutions. From the results of the consideration of the situation in the field, several findings make the authors interested in researching organizational justice, job satisfaction, and organizational commitment on organizational citizenship behavior. This study focuses on one of the private educational institutions of SMA Islam Terpadu X. The total population and sample in this study were 58 respondents. The analytical technique used is structured equation modeling (SEM) with partial least square research tools with data collection methods using questionnaires to all employees. The results of this study are that organizational justice has a significant effect on employee job satisfaction while others do not.